2018
DOI: 10.1097/mpg.0000000000002085
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Norovirus Infections, Coinfections, and Undernutrition in Children From Brazilian Semiarid Region

Abstract: This study highlights the genetic variability of NoV and, associated co-infections and undernutrition in infants from low-income Brazilian semiarid region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…This finding corroborates reports from previously published literature from the MAL-ED birth cohort study, which showed that norovirus GII exhibited a higher attribution burden for diarrhea in the first 2 years of life, compared to norovirus GI [ 8 ]; thus indicating that the prevalence of norovirus GII is indeed greater than that of norovirus GI. A cross-sectional study conducted among young Brazilian children with community acquired diarrhea also reported lower detection of norovirus GI in comparison to norovirus GII, although was not considered in this study [ 12 ]. Moreover, a significant negative association between the viral loads with LAZ and WAZ was found, but this study did not have a longitudinal design and had monthly follow-ups for the assessment of the burden of multiple enteropathogens including norovirus GI and norovirus GII as well as for the subclinical carriage of norovirus [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This finding corroborates reports from previously published literature from the MAL-ED birth cohort study, which showed that norovirus GII exhibited a higher attribution burden for diarrhea in the first 2 years of life, compared to norovirus GI [ 8 ]; thus indicating that the prevalence of norovirus GII is indeed greater than that of norovirus GI. A cross-sectional study conducted among young Brazilian children with community acquired diarrhea also reported lower detection of norovirus GI in comparison to norovirus GII, although was not considered in this study [ 12 ]. Moreover, a significant negative association between the viral loads with LAZ and WAZ was found, but this study did not have a longitudinal design and had monthly follow-ups for the assessment of the burden of multiple enteropathogens including norovirus GI and norovirus GII as well as for the subclinical carriage of norovirus [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…A cross-sectional study conducted among young Brazilian children with community acquired diarrhea also reported lower detection of norovirus GI in comparison to norovirus GII, although was not considered in this study [ 12 ]. Moreover, a significant negative association between the viral loads with LAZ and WAZ was found, but this study did not have a longitudinal design and had monthly follow-ups for the assessment of the burden of multiple enteropathogens including norovirus GI and norovirus GII as well as for the subclinical carriage of norovirus [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Brazil has a continental area with a variety of climatic patterns and population conditions that might reflect distinct patterns of viral circulation and genetic diversity. Regional restricted studies have demonstrated the impact of norovirus in Brazil [ 21 , 22 , 23 ]; however, there is still a gap regarding the burden of AGE caused by norovirus covering different regions and states country-wide. Continuous nationwide surveillance of norovirus-related AGE represents an important tool to understand the epidemiology and disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the polymerase region, the most frequent genotypes were GII.P7 and GII.P16, while based on the capsid region, the main genotypes were GII.3, GII.14, and GII.4 New Orleans_2009. However, when both regions were analyzed, the authors observed a high frequency of recombinant strains classified as GII.P16-GII.3, GII.P7-GII.14, and GII.P7-GII, of which GII.P16-GII.3 had the highest prevalence [26].…”
Section: Northeast Regionmentioning
confidence: 98%